Ahmed Paşa, Dîvân (inceleme-tenkitli metin-çeviri-sözlük) - Hayal, Züleyha (My University, 2022)
15. yüzyıl şâiri Ahmed Paşa biçim ve içeriğe getirdiği yeniliklerle Türk şiirinin dönüm noktalarından biri sayılmıştır. Şâirin tek edebî mirası olan Dîvân çeşitli açılardan ayrıntılı olarak araştırıldı. Tarihî ve edebî planda dil, biçim, içerik, üslûp öğeleri üzerinden şiiri ve şâirliği incelenerek edebiyat tarihindeki yeri araştırıldı. Şiir estetiğini oluşturan unsurlar belirlendi ve değerlendirildi. Tarihî kaynaklar ışığında şâirin bireysel ve toplumsal konumunu, çağıyla ilişkilerini ortaya koyan biyografisi hazırlandı. Zamanla ortaya çıkan yeni divan nüshalarından edisyon kritik için gerekli ve uygun bulunanlar seçilerek Dîvân’ın yeni ve modern bir neşri yapıldı. Yeni edisyonda yapılan güncellemeler sebepleriyle gösterildi. Bu tez, anlam çalışmalarıyla desteklenmiş bir metin neşri modeli üzerinde geliştirildi. Yeni edisyonda Dîvân’ın bütün Türkçe, Arapça ve Farsça manzum yapıları 21. yüzyıl Türkçesine çevrilerek güncel bir tercüme metin oluşturuldu. Dîvân metnindeki bütün söz yapılarının temel, yan ve şiirsel anlamlarını ayrı bölümler halinde gösteren tam bir sözlük hazırlandı. Son bölümde anlama ilişkin alınan diğer notlarla ikinci metnin açıklayıcılığı daha da desteklendi. Çeviri metin ve sözlük, esas metni semantik yapısıyla tartışan incelemeler olarak da görülebilir. Edisyon kritik etrafında gelişen semantik, leksikolojik, estetik ve biyografik araştırma süreçlerinin kapsamı olan tez, eserden döneme uzanan bir bakış açısıyla eski metinleri anlamada ve yorumlamada teklifler sunmakta; Dîvân’a, 15. yüzyıl Türk edebiyatına ve Eski

The 15th century poet Ahmed Pasha was considered one of the turning points of Turkish poetry with the innovations he brought to form and content. Divan, which is the only literary legacy of the poet, has been studied in detail from various perspectives. His place in the history of literature has been tried to be determined by examining his poem and poesy on the basis of language, form, content and style elements in the historical and literary context. The elements that make up the aesthetics of poetry were determined and evaluated. In the light of historical sources, his biography, which reveals the poet’s individual and social position and his relations with his age, has been prepared. A new and modern edition of the Divan was made by choosing the necessary and appropriate ones for the edition critique from the new divan copies that emerged over time. The updates made in the new edition are shown with their reasons. This thesis was developed on a text publication model supported by semantic studies. In the new edition, all Turkish, Arabic and Persian verse structures of the Divan were translated into 21st century Turkish and an up to date translated text was created. A complete dictionary was prepared showing the basic, saminal and poetic meanings of all the word structures in the Divan text in seperate sections. The explanatory nature of the text was further supported by other notes on meaning in the last section. The translated text and dictionary can also be considered as a study that discusses the main text with its semantic aspects. The thesis is the scope of semantic, lexicological, aesthetic and biographical research processes that develop around the edition critique. The thesis, which presents proposals for understanding and interpretation ancient texts with perspective extending from the work to the period, aims to make a new and original contribution to Divan, 15th Century Turkish Literature and Old Turkish Literature studies.
Keywords: Ahmed Paşa; Ahmed Paşa, 1426- 1497; anlam; dictionary; Divan; Dîvân; meaning; poetry; sözlük Ahmed Pasha; şiir; Turkish literature; Turkish poetry; Türk edebiyatı; Türk şiiri